2018
DOI: 10.3390/su10072558
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Lock-Out: Leading the Fossil Port of Rotterdam into Transition

Abstract: Abstract:The port of Rotterdam is a global leader in the fossil fuel economy, with a 50% market share for fossil fuel products in North-Western Europe. Although it is one of the most efficient and innovative ports globally, over the last decade it has seen a gradual increase of pressures on its activities and the need to develop alternative low-carbon strategies. This paper describes how a turbulent energy context, growing societal pressure and a change in the leadership of the Port Authority opened up space f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…It is likely that a range of alternative conceptualisations of radical change would emerge from such a debate, and Kelly et al (2018a) have suggested that an evolutionary framework that draws on the 'Transition Management' approach (Grin, 2010;Loorbach and Rotmans, 2010;Verbong and Loorbach, 2012), could provide a fruitful avenue of exploration. Practical applications of the transitions perspective are already resulting in a transformation of governance approaches to climate change as well as urban and port sustainability (Frantzeskaki et al, 2014;Bosman et al, 2018;Hölscher et al, 2018). In any case, the findings described in this paper have shown that there is a need for a new vision of sustainable marine management that moves beyond reform of existing structures, but whose uncompromising goal should be radical and fundamental transformation of marine governance.…”
Section: By Askingmentioning
confidence: 82%
“…It is likely that a range of alternative conceptualisations of radical change would emerge from such a debate, and Kelly et al (2018a) have suggested that an evolutionary framework that draws on the 'Transition Management' approach (Grin, 2010;Loorbach and Rotmans, 2010;Verbong and Loorbach, 2012), could provide a fruitful avenue of exploration. Practical applications of the transitions perspective are already resulting in a transformation of governance approaches to climate change as well as urban and port sustainability (Frantzeskaki et al, 2014;Bosman et al, 2018;Hölscher et al, 2018). In any case, the findings described in this paper have shown that there is a need for a new vision of sustainable marine management that moves beyond reform of existing structures, but whose uncompromising goal should be radical and fundamental transformation of marine governance.…”
Section: By Askingmentioning
confidence: 82%
“…The analysis focused on strategy to coopt the business community in establishing a radically green energy landscape, and/or with local communities and prosumers to advance a decentralized model of energy transition. As Bosman et al (2018) show in their case study of the port of Rotterdam transition, transitions become feasible as economic and sociopolitical pressures intensify; traditional practices become unsustainable and hence less profitable and legitimate; and some regime actors revisit elements of their strategy. At a time when traditional business models are collapsing, the role of politics is to capitalize on social pressures, ally with those regime actors willing to break loose, and smoothly guide business into more sustainable, legitimate and profitable trajectories by creating demand.…”
Section: Discussionmentioning
confidence: 99%
“…To make matters worse, there is ongoing debate within the EU policy circles on whether renewables should lose their priority access to the grid; if this materializes, incentives for generating renewables will weaken further (Proedrou, ). Such moves, actual and speculative, mirror the resilience of the fossil regime and the pressure it exerts on policy‐making structures to hinder energy transitions (Geels, ; Bosman et al, ). The EU has failed to supplement and empower energy transition pathways with further policy schemes across sectors, involving but not confined to taxation, investment and industrial policy. This said, the EU is investing in the decarbonization of the transport sector.…”
Section: The Prioritization and Securitization Of Gas Importsmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovation is again necessary as we face several transitions, but the OECD claims that the vision should be "imaginative rather than technocratic" (OECD 2014). This will be a major challenge for Rotterdam since the port's regime is still based on scale and volume and its success is measured in throughput (Bosman et al 2018). Since the 1950s, the port's infrastructure has developed to meet the requirements of the petrochemical industry, which has made it very difficult to change focus.…”
Section: The Expansion Of the Port Into The Sea: 1970s-presentmentioning
confidence: 99%